Characterization of a third major SINE family of repetitive sequences in the galago genome. - Daniels, G R (1991)
In addition to the Alu family of short interspersed repetitive DNA elements (SINEs), we have previously characterized one other repetitive DNA family (Type II) in the prosimian, Galago crassicaudatus. We present here a detailed analysis of seventeen members of a third galago SINE family designated as the Monomer family. Both the Monomer and Type II families are shown to be specific for the galago genome as compared to other primates, including another prosimian, the lemur. Moreover, in vitro transcription of galago SINEs suggests that the Monomer and Type II families have appreciably stronger RNA polymerase III promoters than does the Alu family. This agrees with the promoter sequence for each of these SINE families, in that the Monomer and Type II family promoters are more closely related to the RNA polymerase III promoter consensus sequence than is the Alu family promoter. These promoter strength analyses also correlate with copy number and sequence divergence analyses, which suggests that the SINE families with the strongest promoters have been amplified most recently in the galago genome.